Transcranial Direct Current Stimulation Over Dorsolateral Prefrontal Cortex Modulates Risk-Attitude in Motor Decision-Making - Ota, Keiji; Shinya, Masahiro; Kudo, Kazutoshi (Frontiers in Human Neuroscience, 2019)
Humans often face situations requiring a decision about where to throw an object or when to respond to a stimulus under risk. Several behavioral studies have shown that such motor decisions can be suboptimal, which results from a cognitive bias toward risk-seeking behavior. However, brain regions involved in risk-attitude of motor decision-making remain unclear. Here we investigated the role of the dorsolateral prefrontal cortex (DLPFC) in risky motor decisions using transcranial direct current stimulation (tDCS). The experiment comprised a selective timing task requiring participants to make a continuous decision about the timing of their response under the risk of no rewards. The participants performed this task twice in a day: before and while receiving either anodal stimulation over the right DLPFC with cathodal stimulation over the left DLPFC (20 min, 2 mA), cathodal stimulation over the right DLPFC with anodal stimulation over the left DLPFC, or sham stimulation. In line with previous studies, their strategies before the stimulation were biased toward risk-seeking. During anodal stimulation over right DLPFC with cathodal stimulation over left DLPFC, participants showed more a conservative strategy to avoid the risk of no rewards. The additional experiment confirmed that tDCS did not affect the ability of timing control regarding the time intervals at which they aimed to respond. These results suggest a potential role for the DLPFC in modulating action selection in motor decision-making under risk.